Belarus : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2002)
This Selected Issues paper reviews the external competitiveness of the Belarusian economy, particularly in 2000-01. The analysis starts with an overview of developments in Belarus' external current account. The paper then examines various competitiveness indicators, most importantly changes in external and internal real exchange rates, as well as labor cost measures. It reviews trade data by sectors to explain recent export performance. The paper also provides an overview of current wage policy and its macroeconomic effects.